Biomaterials for breast reconstruction: Promises, advances, and challenges. (22nd September 2020) - Abdul‐Al, Mohamed; Zaernia, Amir; Sefat, Farshid
Abstract: Breast reconstruction is the opportunity that provides the chance of having breast after undergoing surgical removal of the breast tissue due to cancer‐related surgery. However, this varies on the stage of the cancer diagnosis and the procedure undertaken. There are many regenerative medicine methods that provide several initiatives and direct solutions to problems such as the development of "bioactive tissue, " which can regenerate adipose tissues with similar normal functions and structures. There have been several studies which have previously explored for the improvement of breast reconstruction including different variations of biomaterials, different fabrication and processing techniques, cells as well as growth factors which enable bioengineers and tissue engineers to reconstruct a suitable breast for patients with breast cancer. Many factors such as shape, proper volume, mechanical properties have been studies but very scattered with not adequate solution for existing patients worldwide. This review article aims to cover recent advances in the biomaterials, which can be used for reconstruction of breasts as well as looking at the various factors that might lead to individuals needing reconstruction and the materials that are available. The focus would be to look at the various biomaterials that are available to use for reconstruction, their properties, and their structural integrity.